Aplicação de biorreatores anaeróbios em diferentes temperaturas para produção de hidrogênio a partir de águas residuárias agroindustriais - Ramos, Lucas Rodrigues (2016)
The present evaluated the influence of hydraulic retention time (HRT), cheese whey substrate concentration, temperature in thermophilic range (55 a 75oC) and cofermentation of sugar cane stillage and cheese whey in continuous hydrogen production in anaerobic fluidized bed reactor (AFBR) and expanded granular sludge bed reactor (EGSB). Seven reactors were used, being three of them in EGSB configuration in mesophilic temperature (30oC) feed in different cheese whey concentrations were inoculated with mesophilic sludge from the poultry slaughterhouse wastewater (RM5, RM15 e RM25). Other four reactors in AFBR configuration, inoculated with thermophilic sludge from the treatment of sugarcane stillage, were operated in thermophilic range. In these it was evaluated the effect of temperature in thermophilic range using as substrate cheese whey (RTS) and sugar cane stillage (RTV). Also, it was evaluated the cofermentation of stillage with cheese whey (RTCV e RTCVS). In the reactors RM5, RM15, RM25, RTS and RTV, it was observed the volumetric H2 production (HPR) and H2 content increase behavior from the HRT decrease. However, there was a decrease in H2 yield (HY) in lower HRT for all reactors, reaching a maximum of 5.51 ± 0.37 mmol.g DQO-1 (RTS). The increase in cheese whey substrate concentration favored the hydrogen production in EGSB reactors, with maximum HPR of 0.312 ± 0.026L H2.h-1.L-1 in the concentration of 25,000mg lactose.L-1 (RM25). The increase in temperature from 55oC to 75oC, the hydrogen production was reduced because of the difficult adaptation of the microbial community originally from a thermophilic sludge. The cofermentation strategy enabled the increase of HY in the HRT of 8h, with a maximum of 0.82 ± 0.07 mmol.g DQO-1 (RTCVS). The main soluble metabolites related to hydrogen production were acetic and butyric acids. On the other hand, higher lactate concentrations were observed in conditions with low hydrogen production.